Biomedical applications of RNA-based devices. (December 2017) - Kim, Cameron M.; Smolke, Christina D.
Abstract: Emergent RNA technologies employ sequence and structural information to perform a diversity of biological functions. Synthetic RNA molecules have been developed for a wide array of applications, including genetic regulation, environmental sensing, and diagnostics devices. Recent advances in chemical synthesis and computational design of RNA have enhanced our ability to program novel functions and expand upon current biomedical applications for therapeutics and diagnostics. In this review, we highlight recent advances in synthetic RNA devices that have been engineered for biomedical systems, while addressing the current limitations and challenges of translating these engineered functional RNAs to clinical applications. Highlights: RNA devices sense environmental cues to control diverse biological outcomes. RNA devices are modular, programmable, and can be integrated into complex systems. RNA can be engineered to exhibit diverse biological functions. Clinical translation of RNA devices remains a significant engineering challenge.